Dimensi Pengukuran Akuntansi Pertanggung Jawaban Sosial Dalam Corporate Social Responsibility Dan Sustainability Reporting - Budianto Tedjasuksmana (Fakultas Ekonomi Universitas Katolik Darma Cendika, 2012)
The topic of social responsibilities reporting usually relates with the responsible for firms to their direct owners (shareholders) alone, or do they owe a duty to the wider community in which they operate. A firm should voluntarily discloses information publicly about its social and environmental performance that implies the managers are acknowledging that they are accountable to abroad group ofstakeholders in relation not to only their financial performance, but also their social and environmental performance. Those environmental aspects should be described in a lot of progress in their social publicly responsibilities reporting, hoping that all shareholders know completely the whole position and financialperformance, risks, business prospects and corporate sustainability. The accountability for these report disclose all aspects that shows measurement of company’s social performance as a key success factor for social performance measurement. Socio Economic Enviromental Accounting is wide-spread concept for firms wishing to realize broader societal and environmental objectives inaddition to increasing shareholdes value.